Design and analysis of a grid-connected hybrid power system with constant supply for Patenga, Bangladesh. Issue 1 (1st January 2020) - Kabir, K. M.; Mazumder, Snehadhit; Chowdhury, Md. Sarwar Uddin; Matin, M. A.; Forhad, Mohammad Wakkas Uddin; Mallick, Anik
Abstract: A quickly growing nation like Bangladesh is experiencing scarcity of efficient electricity production system. Upgrade of the electricity production system is required to keep the progress of the nation uninterrupted. Keeping this motto into consideration, ﻿in this research, a grid-connected hybrid system model has been identified to overcome the shortage of electricity in Bangladesh with the combination of photovoltaic, wind turbines, diesel generator for remote ﻿and upgrade areas. Photovoltaic and wind turbines are used as a main primary source and the diesel generator is kept as a standby source to fulfil our target. The proposed system is mainly the renewable energy-based plant because it is environmentally friendly with less emission carbon as well as other greenhouse gases, as well as the system is controlled by the programmable logic controller for supplying constant electricity. For design, optimization ﻿and grid connection, Patenga beach, Chittagong, Bangladesh has selected where resources are generally usable. Finally, it has been found that the cost of electricity scheme becomes as low as 0.12/kWh compared to the quick rental plant (around 0.33/kWh) in Bangladesh.